2001
DOI: 10.3189/172756501781831819
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen isotopic and soluble ionic composition of a shallow firn core, Inilchek glacier, central Tien Shan

Abstract: data from the core demonstrate the dominant influence of dust deposition on the soluble chemistry at the site, and indicate significant interannual variability in atmospheric-dust loading during the 1990s. Anthropogenic impacts on NH 4 + concentrations are observed at the site, and suggest a summer increase in atmospheric NH 4 + that may be related to regional agricultural (nitrogen-rich fertilizer use) activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 36 publications
(39 reference statements)
7
52
1
Order By: Relevance
“…The significantly different average ratio at Belukha glacier (median Cl À /Na + of 1.0) as well as its strong fluctuation (s = 0.8) are likely caused by the high continentality of the area. Any long-range transport of coarse-mode sea-salt aerosol is highly unlikely, as it is also the case in Tien Shan, northwest China [Kreutz et al, 2001]. Wake et al [1993] reported that sodium and chloride signals in the northeastern regions of the Tibetan Plateau could relate to monsoon precipitation but are effectively masked by sodium and chloride derived from the arid and semi-arid regions in China.…”
Section: Water-soluble Ionic Speciesmentioning
confidence: 99%
See 3 more Smart Citations
“…The significantly different average ratio at Belukha glacier (median Cl À /Na + of 1.0) as well as its strong fluctuation (s = 0.8) are likely caused by the high continentality of the area. Any long-range transport of coarse-mode sea-salt aerosol is highly unlikely, as it is also the case in Tien Shan, northwest China [Kreutz et al, 2001]. Wake et al [1993] reported that sodium and chloride signals in the northeastern regions of the Tibetan Plateau could relate to monsoon precipitation but are effectively masked by sodium and chloride derived from the arid and semi-arid regions in China.…”
Section: Water-soluble Ionic Speciesmentioning
confidence: 99%
“…[22] Terrestrial dust has been postulated as the main source of sulfate and nitrate in Tien Shan snow [Wake et al, 1990;Williams et al, 1992;Sun et al, 1998;Kreutz et al, 2001]. The differing temporal trends observed for sulfate, nitrate and calcium suggest that dust is not the only source of those two anions in the Belukha region.…”
Section: Water-soluble Ionic Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Zdanowicz et al (2012) Arctic Canada 2 560 0.3-0.6 polyth. Kreutz et al (2001) Tien method. Eight (Gries) and six (Silvretta) DEMs are available over the last five decades, documenting changes in glacier area and volume (Bauder et al, 2007).…”
Section: Glacier Geometrymentioning
confidence: 99%